Main oral and dental changes in patients with diabetes mellitus - Bárbara Olaydis Hechavarría Martínez; Leonardo Núñez Antúnez; Milagros Fernández Toledo; Noraida Cobas Pérez (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and cross-sectional study of 126 patients with diabetes mellitus types 1 and 2 assisted in the Center for Care to the Diabetic Patient was carried out from January to March, 2016, aimed at determining the oral and dental changes present in them.  The female sex, diabetics type 2, the lost teeth, inadequate oral hygiene, advanced periodontopathy, as well as the xerostomy as the most common oral change and hypertension as associated disease prevailed in the series. It is recommended to carry out educational strategies to increase the health knowledge of the population, in order to avoid future complications and to motivate the realization of new scientific investigations that allow the improvement of the oral and general health.